La crisis de la voz poética en El hilo atroz (2021) de Beverly Pérez Rego - Aguirre-Bernal, Miguel (2024)
In El hilo atroz (2021), Beverly Pérez Rego equates writing with weaving and, from there, proposes a crisis of the poetic voice that involves three levels of depth: literary tradition, the poetic subject, and artistic creation. This paper intends to explore the implications of this metaphor and analyze the different modulations that the crisis adopts throughout the collection of poems. These inflections are revealed to be very much in line with the assumptions of postmodernism and end up developing a hyper and intertextual writing made from rags. It concludes by demonstrating how the author postulates the erasure of tradition –the cutting of the hilo atroz– as a literary necessity, in what we call an imperative of destruction.